2018
DOI: 10.1016/j.physletb.2018.06.057
|View full text |Cite
|
Sign up to set email alerts
|

Braids, normed division algebras, and Standard Model symmetries

Abstract: This paper represents a first attempt at unifying two promising attempts to understand the origin of the internal symmetries of leptons and quarks. It is shown that each of the four normed division algebras over the reals admits a representation of a circular braid group. For the complex numbers and the quaternions, the represented circular braid groups are B 2 and B c 3 , precisely those used to construct leptons and quarks as framed braids in the Helon model of Bilson-Thompson. It is then shown that these fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…Besides giving a particularly aesthetic embedding of one generations of fermions into minimal ideals of C (10), our model also provides a clear pathway for extending earlier work [8] which established a curious structural similarity between the basis states of the minimal left ideals of C (6) and certain braids used in a topological model of leptons and quarks [9]. Incorporating the results of the present paper to extend these earlier results to include the weak interaction will be the focus of another paper [10].…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Besides giving a particularly aesthetic embedding of one generations of fermions into minimal ideals of C (10), our model also provides a clear pathway for extending earlier work [8] which established a curious structural similarity between the basis states of the minimal left ideals of C (6) and certain braids used in a topological model of leptons and quarks [9]. Incorporating the results of the present paper to extend these earlier results to include the weak interaction will be the focus of another paper [10].…”
Section: Introductionmentioning
confidence: 78%
“…The motivation for this work came from the results of [8] which showed that there is a one-to-one correspondence between the basis states of the minimal left ideals of C (6) and the braided states in the topological model proposed in [9]. 5 To be able to extend this curious structural similarity to include the weak force, the underlying electrocolor structure generated from C (6) should remain intact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finding a theoretical basis for the mathematical structure that underlies the SM remains a prominent challenge in physics. Instead of the common approach of embedding the SM gauge group into some larger group, recently there has been an interest in using the fundamental and generative structures of the four normed division algebras as a simple mathematical framework for particle physics [1,2,3,4,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In the loop structure of telomeres [7], there exist layers of G-quadruplex (G4) [15]. Their structures are similar to the structure with the loop braid group in the standard model [16,17]. The G letter (guanine) can be suitably chosen as the hidden time scale in a biological clock.…”
Section: Introductionmentioning
confidence: 99%